DATA PROCESSING OF PLATES CONTAINING IMAGES OF URANUS AND NEPTUNE FROM UKRVO DIGITAL ARCHIVE: STRUCTURE, QUALITY ANALYSIS - Protsyuk, Yu.; Yizhakevych, O.; Kovylianska, O.; Protsyuk, S.; Andruk, V.; Kashuba, S.; Kazantseva, L. (Одеські астрономічні публікації, 2016)
To use accumulated resources of UkrVO digital archive, analysis of the available photographic plates containing images of Uranus and Neptune was conducted. Data processing of selected plates was also caried out to provide an estimate of positional precision and accuracy. Archives of the Research Institute: Nikolaev Astronomical Observatory (NAO), Main Astronomical Observatory of National Academy of Science (MAO), Astronomical Observatory of Odessa National University (AO ONU), Astronomical Observatory of Kyiv National University (AO KNU) were used. Numbers of plates containing images of Uranus and Neptune are, respectively, the following: 220 and 218 plates in NAO, 64 and 35 plates in MAO, 54 and 44 plates in AO ONU, 3 and 1 in AO KNU. Plates of NAO and MAO have 2 or 3 exposures per plate, and other plates have only one exposure per plate. The epoch of observation for most plates is 1960 to 1998, and for only one plate is 1908. All plates were scanned with the resolution not less than 1200 dpi. Each plate of NAO was scanned 5 to 6 times. Plates containing images of Uranus and Neptune were, respectively, scanned 618 and 952 times in NAO. All plates of other observatories were scanned only once. Raw image processing for scans containing images of Uranus and Neptune was conducted for all scans obtained in observatories. (X, Y) coordinates, (I) intensities and FWHM values were obtained for images of all objects. Star identification for scans containing images of Uranus and Neptune was, respectively, conducted for 600 and 936 scans in NAO and for 71 scans in MAO. Coordinates of all objects were obtained. Positional accuracy of reference stars was estimated for 244 plates of NAO and 66 plates of MAO, and has value of 0.08″-0.26″.